EXPLORATORY DESIGN AND ANALYSIS ON CUSTOMER PREFERENCE ON WEBTOON ADAPTATION SHORT MOVIE: A CASE STUDY OF 10 PM - Anthony, Egan; Eryc, Eryc (INFOKUM, 2022)
This study aims to explore customer preferences for adapting a webtoon into a short film with a case study on the film 10 PM. The research was conducted using the FGD (Focus Group Discussion) method involving a number of respondents who had experience watching the short film 10 PM. The results of the study show that respondents like the horror genre as an option for short films and are satisfied with the ending of the story which solves the main mystery. In addition, respondents also provided input regarding character development and improving production quality, such as using more sinister makeup and selecting the right actors. In this case, the research results can provide views and recommendations for film producers and content creators to produce works that are better and in accordance with customer preferences. This research also shows the importance of listening to feedback from customers in developing a product. By understanding customer preferences, producers and content creators can adapt their production to meet customer needs and wants. Apart from that, this research also contributes to the development of knowledge about the production of audio-visual content in Indonesia, especially in the ever-growing horror genre.